Kemampuan Literasi Digital pada Jenjang SMA/SMK dalam Mengurangi Penyebaran Hoax - Dea Apriliani Rahman; Fanda Setia Ningrum; Najmi Annidia Nurfadilah; Ratu Wesnisi’an Hurni (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The spread of hoaxes among hight school/vocational school children is vulnerable, because at the time, they are still in their teenage years, during which time people easily believe and are still unstable in determining what is right and wrong. This research aims to find out how the digital literacy skills of high school/vocational school teenagers can reduce the spread of hoaxes. The type of research carried out was a descriptive quantitative approach, with a total sampling technique with a sample of 112 respondens. Meanwhle, the research instrument used was a questionnaire. The research shows that the digital literacy of high school/vocational school and equivalent teenagers is generally quite good and is in the medium category, which is characterized by moderate digital literacy skills, 61% of the 112 respondens.